Finding a place to be our-selves: Narratives of young black women activists - Bradbury, J.; Mashigo, T. (South African Journal of Higher Education, 2018)
This article explores narrative identity constructions of black women student activists in contemporary South Africa. The apartheid past is evidently alive in the politics of the present and in the embodied experiences of these young women but mutates and is appropriated in new ways. In some senses, these women now occupy the centre rather than the periphery; many living in middle-class suburbs, studying and occupying leadership positions in increasingly de-racialised spaces. However, their narratives reveal the precarity of these identities in relation to 1) male student activists; 2) fellow students, both black and white; and 3) the wider civil society of the working class and unemployed poor. These stories were collected prior to the decolonising political moment of #FeesMustFall but provide prescient insight into the intersectional positionality of young black women student activists in the Higher Education landscape of South Africa today.